A Learning-Based Automotive Sound Field Reproduction Method Using Plane-Wave Decomposition and Multi-Position Constraint - Qian, Yufan; Xihong Wu; Tianshu Qu (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2026)
Achieving sound field reproduction (SFR) with high sound quality and accurate spatial localization in automotive cabins is particularly challenging due to complex acoustics and constrained loudspeaker layouts. This paper proposes a learning-based method to address this challenge, integrating a spatial domain physics-informed constraint based on plane-wave decomposition (PWD) with a multi-position control strategy. Results from both objective evaluations and in-situ subjective listening tests consistently validated the superiority of the proposed approach over several baseline methods. Moreover, we show that the correlation of spatial power maps (SPMs) derived from PWD provides a reliable objective metric that closely reflects perceived spatial localization in the cabin environment.